Analysis of the Influence of Brand Image and Store Atmosphere on Consumer Purchasing Decisions at Coffee Shops in Jakarta - Hendy Tannady; Yohanes Totok Suyoto; Magdalena (Formosa Journal of Sustainable Research, 2022)
This research was conducted to analyze the most influential factors on purchasing decisions at Stuja coffee shop. The factors that will be examined are the atmosphere of the store and brand image which are felt to contribute quite a bit in making purchasing decisions by consumers. This study uses sample data from 200 respondents who have purchased coffee at Stuja Kopi Jakarta throughout 2022. The results of this study indicate that store convenience and brand image are the factors that most influence purchasing decisions. Easy information discovery can make consumers more familiar with the coffee products offered so that the decision to buy coffee products at Stuja Kopi Jakarta is even greater